Individual risk factors for possible undetected dementia amongst community-dwelling older people in New Zealand. (April 2020) - Martinez-Ruiz, Adrian; Huang, Ying; Gee, Susan; Jamieson, Hamish; Cheung, Gary
There is general acknowledgement of the importance of early diagnosis of dementia, yet there are still high rates of undetected dementia internationally. The aim of this cross-sectional study was to determine the sociodemographic characteristics associated with possible undetected dementia in a large sample of community-dwelling older New Zealanders. The sample consisted of older people (age ≥ 65) who had received the homecare version of the international Residential Home Care Assessment version 9.1 over a two-year period and who were screened positive for possible dementia on the international Residential Assessment's Cognitive Performance Scale. People with possible alternative explanations for impaired cognitive performance such as depression and other neurological conditions were excluded from analysis. The 5202 eligible individuals were categorized into two groups: (1) those with a recorded diagnosis of dementia (64%) and (2) those without a recorded diagnosis of dementia (i.e. possible undetected dementia group) (36%). Logistic regression was used to evaluate the association between individual characteristics and possible undetected dementia. Significant risk factors for being in the possible undetected dementia group included Asian ethnicity, living alone, not having participated in long-standing social activities recently, major life stressors, and limited accessibility of their house. The knowledge gained from this study could enable targeting of services and resources for the groups at risk of undetected dementia to have a more equitable access to early diagnosis.